POSSIBILITIES OF MULTISPIRAL COMPUTED TOMOGRAPHY IN ASSESSING THE STATE OF A PSEUDOCAPSULE OF A KIDNEY TUMOR AND IN CHOOSING THE METHOD OF ORGAN-PRESERVING SURGERY IN CLINICALLY LOCALIZED RENAL CELL CARCINOM - Filimonova E. S.; Aleshkevich A. I. (Žurnal Grodnenskogo Gosudarstvennogo Medicinskogo Universiteta, 2020)
Background. The margin from the edge of the tumor to the area of intact kidney tissue is today a frequently discussed issue in the surgical treatment of patients with localized renal cell carcinoma. Based on the results of recent epidemiological and clinical-morphological studies, it became necessary to create a new complex of nephrometric assessment of a kidney tumor to select the nepron-sparing surgery. Objective: to develop a nephrometric complex for assessing the main characteristics of a kidney tumor node according to multispiral computed tomography data when choosing an organ-preserving surgery method to maintain the maximum amount of healthy kidney tissue and optimize the functional recovery of nephrons after surgical treatment of clinically localized renal cell carcinoma. Material and methods. The material for the study was the data of diagnostics and surgical treatment of 128 patients who underwent organ-preserving surgery. All CT-examinations were performed on an X-ray computer tomograph (General Electric (GE Healthcare), model CT660, 64-spiral system with IQ Enhance technology). Results and Conclusions. The study revealed that the developed diagnostic complex had a statistically significant effect on the prediction and assessment of the anatomical complexity of resection and enucleoresection (p<0.05). It was established that the developed nephrometric assessment of a kidney tumor according to CT-data is an important technical condition for the implementation of a specific method in the absence of indentation from the edge of the tumor pseudocapsule (p<0.002). High equivalent rates of disease-free and tumor-specific survival were also achieved in the observation subgroups in which resection and enucleoresection were performed.